Bacillus amyloliquefaciens PS35 ISOLATED FROM FAT AND OIL CONTAMINATED SITES: AUGMENTATION OF LIPASE PRODUCTION USING STATISTICAL EXPERIMENTAL DESIGN - KANMANI PALANISAMY,; DHIVYA PRIYA BOOPATHY,; KUMARESAN KUPPAMUTHU,; ARAVIND JEYASEELAN, (International Journal of Pharma and Bio Sciences, 2016)
Lipase is an industrially important enzyme and is hence being extensively researched. Novel lipolytic bacterial strains capable of producing lipases with industrially useful properties are the need of the hour. In the present investigation, 52 bacterial strains were isolated from soil and wastewater samples high in fat and oil contents, out of which 12 showed significant lipolytic activity. The best lipase producing strain PS35 was identified to be Bacillus amyloliquefaciens by 16S rRNA gene sequencing. A temperature of 40°C and pH 8.0 were found to be the optimum conditions for lipase production by the strain. Dextrose, sunflower oil and casein were the chemical components in the culture medium that were conducive for lipase production. Subsequently, Box Behnken Design of Response Surface Methodology was applied and the model resulted in 1.44-fold increase in enzyme production. Analysis of variance indicated significance of the proposed model (p < 0.0001) and a good correlation between the experimental and predicted values. This study opens up promising avenues for further research on the properties of this enzyme, based on which appropriate applications could be devised.